Vitamin D Promotes Trophoblast Cell Induced Separation of Vascular Smooth Muscle Cells in Vascular Remodeling via Induction of G-CSF - Zhang, Joy Yue; Wu, Peihuang; Chen, Danyang; Ning, Fen; Lu, Qinsheng; Qiu, Xiu; Hewison, Martin; Tamblyn, Jennifer A.; Kilby, Mark D.; Lash, Gendie E. (Frontiers in Cell and Developmental Biology, 2020)
Vitamin D deficiency is associated with complications of pregnancy such as pre-eclampsia, fetal growth restriction, and miscarriage, all of which are also associated with incomplete spiral artery (SpA) remodeling. We have previously shown that both uterine natural killer (uNK) cells and extravillous trophoblast cells (EVT) are required for successful SpA remodeling, but whether their activity in this process is modulated by vitamin D is not known. In the current study, we use a previously described chorionic plate artery (CPA) ex vivo model of vascular remodeling to determine the effects of 1,25(OH)2D treated uNK cell, placental explant (PEx), and uNK/PEx conditioned medium (CM) on vascular smooth muscle cell (VSMC) disorganization and phenotypic switching. Significant results were followed up in VSMCs in vitro. We demonstrate that 1,25(OH)2D can enhance the ability of PEx to induce SpA remodeling, via a mechanism associated with increased secretion of granulocyte-colony stimulating factor (G-CSF). G-CSF appears able to increase VSMC disorganization and phenotypic switching in both an ex vivo vascular model and in vitro VSMC cultures. The clinical relevance of these findings are still to be determined. G-CSF may have differential effects depending on dose and vascular bed, and vitamin D may play a role in potentiating these actions. G-CSF may be an interesting potential therapeutic target for facilitating physiological vascular remodeling for the prevention of adverse obstetric outcomes.